Aksara jawi: Makna dan fungsi - Noriah Mohamed, (Universiti Kebangsaan Malaysia, 2001)
The Jawi Jawa aksara is known as Pegon alphabet or Arab Gundul and was first used after the encounter with Islam. There had been adjustments in pronounciations to suit the Javanese tongue, nonetheless the originality of the alphabet was preserved. The Jawi aksara did not only serve as a medium of knowledge, but also as a means of fulfillment of meaningful life such as to afford finding one’s right partner in marriage, in healing and even to how to make one’s business enterprising. In reality aksara Jawi tries to search a symbiosis with the function of Alif deemed as a means to be close to God